Diversity of the genus Orthoseira Thwaites (Bacillariophyceae) from Southeast Asia and Rapa Nui Island with descriptions of four new taxa. Issue 1 (2nd January 2022) - Rybak, Mateusz; Glushchenko, Anton; Witkowski, Andrzej; Lange-Bertalot, Horst; Kulikovskiy, Maxim
Abstract : The genus Orthoseira Thwaites contains centric diatoms typically inhabiting marginal-aquatic or terrestrial habitats. The high morphological plasticity of representatives of the genus and their occurrence in rarely studied terrestrial habitats complicates an overall assessment of their biodiversity and the distribution of particular species. This study presents a description of four new species of this genus from Southeast Asia and Easter Island. They include: O. radiata M.Rybak, Glushchenko & Kulikovskiy sp. nov., O. distincteareolata M.Rybak, Glushchenko & Kulikovskiy sp. nov., O. cylindrica M.Rybak, Glushchenko & Kulikovskiy sp. nov. and Orthoseira rapanuiensis M.Rybak, Witkowski & Lange-Bertalot sp. nov. Additionally, we attempt to provide a solution to the confused taxonomical history of Liparogyra circularis Ehrenberg and provide the first detailed description of Orthoseira tropica (Krasske) Metzeltin & Lange-Bertalot.